Characterization and simulation of fast neutron detectors based on surface-barrier VPE GaAs structures with polyethylene converter. (5th December 2016) - Chernykh, A.V.; Chernykh, S.V.; Baryshnikov, F.M.; Didenko, S.I.; Burtebayev, N.; Britvich, G.I.; Kostin, M.Yu.; Chubenko, A.P.; Nassurlla, Marzhan; Nassurlla, Maulen; Kerimkulov, Zh.; Zholdybayev, T.; et al.
Abstract: Fast neutron detectors with an active area of 80 mm 2 based on surface-barrier VPE GaAs structures were fabricated and tested. Polyethylene with density of 0.90 g/cm 3 was used as a converter layer. The recoil-proton surface-barrier sensor was fabricated on high purity VPE GaAs epilayers with a thickness of 50 μ m. The neutron detection efficiency measured with a 241 Am-Be source was 1.30 · 10 −3 puls./neutr. for the PE converter thickness of 670 μ m. The signal-to-gamma-background ratio was at the level of 50. Simulation of the detector characteristics with Geant4 toolkit has showed good correlation with the experimental data and allowed to estimate the maximal theoretical detection efficiency of the detector which is determined by the PE converter and equals to 1.37 · 10 −3 puls./neutr. The difference between the measured and simulated values of the detection efficiency is due to the fact that the events with energies below 0.5 MeV were not taken into account during the measurements.